A critical appraisal of Covid-19 in Malaysia and beyond - Abdullah, Jafri Malin; Wan Ismail, Wan Faisham Nu’man; Mohamad, Irfan; Ab Razak, Asrenee; Harun, Azian; Musa, Kamarul Imran; Lee, Yeong Yeh (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2020)
When the first report of COVID-19 appeared in December 2019 from Wuhan, China, the world unknowingly perceived this as another flu-like illness. Many were surprised at the extreme steps that China had subsequently taken to seal Wuhan from the rest of the world. However, by February 2020, the SARS-CoV-2 virus, which causes COVID-19, had spread so quickly across the globe that the World Health Organization officially declared COVID-19 a pandemic. COVID-19 is not the first pandemic the world has seen, so what makes it so unique in Malaysia, is discussed to avoid a future coronacoma.